2023
DOI: 10.1101/2023.02.15.23285928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABAergic regulation of auditory repetition suppression in adults with and without Autism Spectrum Disorder

Abstract: Suppressing responses to repetitive sounds, while staying vigilant to rare sounds, is a cross-species trait vital for survival, which is altered in autism spectrum disorder (ASD). Preclinical models implicate ϒ-aminobutyric acid (GABA) in this process. Although differences in GABA genes, post-mortem markers and bulk tissue GABA levels have been observed in ASD, the link between GABA and auditory processing in humans (with or without ASD) is largely correlational. Here, we directly evaluated the role of GABA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…A conventional auditory oddball paradigm (mismatch negativity, MMN) 62 will be used to passively measure 'repetition suppression' (or habituation) to repetitive auditory stimuli and response to an unexpected 'deviant' stimulus (the eventrelated mismatch negativity MMN response). We and others have observed less repetition suppression in both eight-month-old infants who go on to receive a diagnosis or autism, and adults with a diagnosis of autism 24,30 . Thus, this signal appears linked to autism across infancy to maturity.…”
Section: Auditory Domainmentioning
confidence: 47%
See 1 more Smart Citation
“…A conventional auditory oddball paradigm (mismatch negativity, MMN) 62 will be used to passively measure 'repetition suppression' (or habituation) to repetitive auditory stimuli and response to an unexpected 'deviant' stimulus (the eventrelated mismatch negativity MMN response). We and others have observed less repetition suppression in both eight-month-old infants who go on to receive a diagnosis or autism, and adults with a diagnosis of autism 24,30 . Thus, this signal appears linked to autism across infancy to maturity.…”
Section: Auditory Domainmentioning
confidence: 47%
“…We have also used EEG recordings during sensory stimulation to capture response to GABAB receptor agonist, arbaclofen. We have been able to quantify individual 'shifts' in these measures in response to drug challenge and differences at group-level between autistic and non-autistic participants 10,30 . The range of measures used to capture 'shift' and their target level of brain organisation is shown in Figure 1.…”
Section: Measuring 'Shift'mentioning
confidence: 99%
“…Within this framework, repeated and/or irrelevant sensory inputs might not be inhibited in autism as they would be in TD, resulting in a more robust neural response to these repeated stimuli (Ethridge et al, 2016;Kolesnik et al, 2019). There is evidence from typically developing individuals linking inhibitory processing and habituation (Palermo et al, 2011), and recent evidence suggests that arbaclofen, a GABA receptor agonist, appears to enhance repetition suppression in autistic adults (Huang et al, 2023). Moreover, decreased inhibition in the auditory cortex has been shown in animal models to directly lead to loudness hyperacusis, a form of sound intolerance (McGill et al, 2023).…”
Section: Explanations For Habituation Differencesmentioning
confidence: 99%
“…Correlations, however, are not causal. A more direct way to establish that a particular neurosignaling system is involved in specific sensory mechanisms is to challenge it through pharmacological modulation and observe a change in function ( Whelan et al, 2023 ). We have adopted this approach and previously shown that a single dose of the GABA type B (GABA B ) receptor agonist arbaclofen (STX209) enhances suppression of cortical electroencephalogram (EEG) responses to sensory stimuli in both the visual and auditory domains in individuals with ASD, but does the opposite in nonautistic people ( Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%